Strength and ductility of gradient structured copper obtained by surface mechanical attrition treatment. (5th September 2016) - Yin, Zhe; Yang, Xincheng; Ma, Xiaolong; Moering, Jordan; Yang, Jian; Gong, Yulan; Zhu, Yuntian; Zhu, Xinkun
Abstract: By using surface mechanical attrition treatment (SMAT) at room temperature, a gradient structure (GS) is generated in the surface layer of bulk pure copper samples, which exhibits good uniform elongation and high yield strength simultaneously. Changing SMAT processing time leads to different gradient structures with various component fractions and therefore tune their mechanical properties. The yield strength of the SMAT samples is much higher than the sum of standalone GS layer and coarse-grained (CG) matrix, indicating a synergetic strengthening. Repeated stress relaxation tests were performed to characterize the evolution of mobile dislocations. It was found that the relative mobile dislocation density of SMAT processed sample first drops and then increases with increasing tensile strain. The evolution of mobile dislocations correlates well with strain-hardening evolution. These observations provide insight for the superior combination of high strength and good ductility in SMAT samples. Graphical abstract: Highlights: A gradient structure (GS) was generated in the surface layer of copper, exhibiting superior strength–ductility synergy. The effect of grain size gradient in surface layer on the mechanical properties of sample was investigated. The evolution of mobile dislocation and corresponding deformation mechanisms was explored by stress relaxation tests. An optimum component fraction of GS to tune the strength and ductility to achieve superior properties was discussed.